RESTRUKTURISASI KREDIT BANK KONVENSIONAL DAN BANK SYARIAH PADA MASA PANDEMI COVID-19 BERDASARKAN POJK NO 11/POJK.03/2020 - Yoanfica Risfayeza,; Wardani Rizkianti, SH., MH., (2021)
As a result of the covid-19 pandemic, there is a decline in the economy of business actors, both micro, small and medium enterprises (UMKM). Decreased income for debtors can cause problems in credit financing activities, thus potentially disrupting banking performance and financial system stability which can affect economic growth. Banks as creditors can make efforts to save debtor credit by restructuring credit in accordance with OJK Regulation No.11 / POJK.03 / 2020 concerning National Economic Stimulus as a Countercylical Policy Impact of the Spread of Corona Virus Disease 2019. The purpose of this study is to determine the implementation credit restructuring during the covid-19 pandemic based on POJK No. 11 / POJK.03 / 2020 and the implementation of credit restructuring between conventional banks and Islamic banks during the Covid-19 pandemic. The research method used is normative juridical. The result of this research is that banks can implement restructuring policies on their customers. The provision of this retrofit policy can be implemented on credit or financing provided before or after the debtor is affected by the spread of Covid-19, including UMKM debtors. Conventional banks and Islamic banks offer relief to customers affected by Covid-19 in the form of delaying payment of obligations. The relief given will later be adjusted to the condition of the debtor or the condition of the debtor's business so that it is easier and less burdensome for the debtor11/POJK.03/2020